Perancangan Sistem Pencatatan Penjualan pada Usaha Kebab BosQue99 Secara Digital - Henik Hastuti; Dela Novitasari; Edy Susena (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
In today's digital era, the use of manual sales recording systems is considered ineffective and inefficient. Manual systems often cause various problems, such as calculation errors, delays in reporting, and a lack of accuracy and efficiency in transaction data management. Furthermore, manual recording processes also take longer and are susceptible to data loss. Therefore, a digitalized sales recording system is needed that can be accessed practically, including via mobile devices such as mobile phones. This study aims to design a mobile application-based sales recording system that is fast, easy to use, and able to minimize recording errors. This application is designed to automatically calculate total sales, store transaction data securely, and generate sales reports that can be accessed directly without the need for additional systems. Thus, business owners can record and monitor sales more efficiently and in real time. The methodology used in this study includes data collection methods through interviews and observations of micro and small business owners, as well as a system development method using the Waterfall model, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The result of this research is a system design that includes several key features: a login page for user security, a product menu list page, a transaction input page, and a sales report page that can be downloaded in Excel format. This system design was successfully developed and deemed feasible for implementation in business operations. It is hoped that this application can help business owners improve the efficiency of recording and managing sales data digitally and practically.